Disaggregating Violence: Understanding the Decline - Skott, Sara (Journal of interpersonal violence, 2021)
Although trends of violent crime have been examined for over a century, no previous study has examined the change of subtypes of violence over time. This study therefore aims to identify subtypes of violence in Scotland, where violence levels have decreased from one of the highest in Europe to one of the lowest, based on variables relating to the victim, offender, and incident, and to examine how these subtypes have changed over time. Four main types of violence were identified using multilevel latent class analysis on Scottish Crime and Justice Survey data: public no weapon, public weapon, work-related, and domestic. The findings show that although all types of violence have demonstrated an absolute decrease over time, Domestic and work-related violence have demonstrated relative increases over time. The findings are discussed in relation to the inequality of this decrease and propose guidelines for future prevention policies.